OUTCOMES OF DIRECT PULP CAPPING DONE BY DEFERENT MATERIALS IN PERMANENT TEETH: AFTER 1 YEAR RECALL - Dr. Saad Ali Sabrah; Dr. Mohammed Thamer Alqahtan (Medico Research Chronicles, 2017)
Aim: This study is aimed to compare the prognosis between deferent direct pulp capping materials (CH, MTA, and Biodentine) in permanent teeth of Saudi population after the 1-year recall. Methods: Randomized patient samples were collected in armed forces hospital – dental department included 72 patients between 18 and 40 years old. They were divided into 3 groups according to the materials of direct pulp capping (CH 24patients), (Biodentine 24 patients), or (mineral trioxide aggregate [MTA] 24 patients). After one year recall, the patients were diagnosed clinically and radiographically using the Fisher exact test. Results: No clear deference were detected between CH, MTA, and biodentine in terms of failure of the total of 72 teeth, only 2 recorded failures, 1 of each group(CH, MTA) except dentine. CH : 1:24 MTA : 1:24 Biodentine : 0:24 Biodentine has no inflammatory pulpal response compared to CH and MTA . Conclusion: This study shows no significant difference between the deferent types of direct pulp capping materials. biodentine shows better properties in direct pulp capping compared to CH and MTA and has no failure cases recorded.